Dinamika Pemilihan Variabel Input-Output Pada Penelitian Efisiensi Perbankan Syariah di Indonesia - Syachrul Wahyudi; Andri Soemitra (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
Islamic banking is the backbone of a justice economy. Economic growth requires efficient Islamic banking, costly and profitly. This paper is a literature review that aims to investigate the dynamics of input and output variables in Islamic banking efficiency research in Indonesia. The sample data used were 65 journal papers selected purposively with the initial assistance of the Publish or Perish software. The time span of the publication year of the sample paper is 2007-2021. The analytical method used is bibliometric and content analysis. From the results of the analysis found the existence of dynamics in the selection of input and output variables in research on the efficiency of Islamic banking in Indonesia. There is a tendency for research on the efficiency of Indonesian Islamic banking that leads to the selection of approaches , certain input variables and output variables, namely the intermediary approach. Deposits, labor costs, fixed assets, operational costs, and total assets became the five main rankings of the input variables chosen by researchers throughout the year of publication. From the output point of view, financing and operating income are the two dominant variables that are often used. The selection of methods, approaches, and input-output variables of Islamic banking efficiency research is highly dependent on the level of preference of each researcher. In the end, there were at least two gaps that were found, which could become opportunities for future research on the efficiency of Islamic banking, namely: 1) not absorbing the elements of banking modernity, and 2) not touching the Islamic values ​​that inherently becomes the face of Islamic banking in the implementation of daily operations. Keywords: Islamic banking, Literature review, Input variable, Output variable, Efficiency